Etika Guru dalam Pendidikan Islam: (Studi Komparasi Atas Pemikiran Imam Al-Ghazali Dengan Kh. Hasyim Asy’ari) - Zaini, Bahruddin (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2019)
The writing of this paper aims to describe the ethics of teachers in Islamic education, which involves the thoughts of Imam Al-Ghazali and KH. Hasyim Ash'ari. As for the background of this writing because at this time it is not uncommon for an educator to not have an ethics of wisdom and policy both for students and for themselves. So many cases that arise in the educational environment that we often hear in electronic news or newspapers about the treatment of educators who do not reflect themselves as an educator. In addition, in the world of Islamic education now an educator is more likely to prioritize world happiness and put aside happiness in the afterlife. Therefore, the leaders of Imam Al-Ghazali and KH. Hasyim Asy'ari explained about some ethics that must be considered in Islamic education and must be reflected in an educator to improve Islamic Education in the future. This type of research is library research with 2 Prima data sources, namely the book Ihya 'Ulumuddin and the Book of Adab al-aliim wa al-Muta'llim. This research uses a historical approach. Data analysis techniques using comparative analysis. From the results of the research conducted concluded that: 1) according to Imam al-Ghazali a teacher must be compassionate to students, imitate the behavior of the Prophet Muhammad, as a guide, be open, practice knowledge. 2) according to Khas Hasyim Asy'ari, a teacher must adhere to Allah, as an advisor or guide, implement Islamic law, take advantage of free time by worshiping and compiling papers, seeking the pleasure of Allah. 3) the similarity of the vguru ethics of the two figures is, they have the same view that a teacher must be muraqabah to God, as a guide ,. The difference, in terms of holding the scientific mandate of God, according to Imam al-Ghazali must be the example of the Messenger of Allah, while according to Kh Hashim it is not permissible to obtain office, rank, wealth and popularity. And much more. From this research, there are some suggestions that can improve the concept of a teacher, that it is hoped that a teacher always becomes a role model for students, therefore a teacher must pay attention to their behaviors. So that the goal of Islamic education which is aspired can be achieved. Keywords: Ethics, Teachers, Islamic Education